Gestational ketogenic diet programs brain structure and susceptibility to depression & anxiety in the adult mouse offspring. Issue 2 (29th December 2014) - Sussman, Dafna; Germann, Jurgen; Henkelman, Mark
Abstract Introduction The ketogenic diet (KD) has seen an increase in popularity for clinical and non‐clinical purposes, leading to rise in concern about the diet's impact on following generations. The KD is known to have a neurological effect, suggesting that exposure to it during prenatal brain development may alter neuro‐anatomy. Studies have also indicated that the KD has an anti‐depressant effect on the consumer. However, it is unclear whether any neuro‐anatomical and/or behavioral changes would occur in the offspring and persist into adulthood. Methods To fill this knowledge gap we assessed the brain morphology and behavior of 8‐week‐old young‐adult CD‐1 mice, who were exposed to the KD in utero, and were fed only a standard‐diet (SD) in postnatal life. Standardized neuro‐behavior tests included the Open‐Field, Forced‐Swim, and Exercise Wheel tests, and were followed by post‐mortem Magnetic Resonance Imaging (MRI) to assess brain anatomy. Results The adult KD offspring exhibit reduced susceptibility to anxiety and depression, and elevated physical activity level when compared with controls exposed to the SD both in utero and postnatally. Many neuro‐anatomical differences exist between the KD offspring and controls, including, for example, a cerebellar volumetric enlargement by 4.8%, a hypothalamic reduction by 1.39%, and a corpus callosum reduction by 4.77%, as computed relative to total brain volume. Conclusions These results suggest that prenatal exposure to the KD programs the offspring neuro‐anatomy and influences their behavior in adulthood.